KONSEP PENDIDIKAN ISLAM INTEGRATIF DALAM IDEOLOGI LIBERALISME - Akhmad Zaini (Akademika, 2021)
Liberalization of education is an educational ideology that is student-oriented, so that the long-term goal of education is to preserve and improve the existing social order by teaching each student how to deal with problems in his own life effectively. The concept of liberalism on education implicitly leads to the concept of integrative education "in line with Islamic education", where educational liberalism emphasizes the principle of problem solving when referring to the main concept of educational liberalism, the expected goal is about integration between theory and practice. Specifically, the concept of integrative Islamic education in liberalism ideology is seen through several things such as; foundation, objectives, methods and evaluation.